Building Santri Character Through Leadership Based on Islamic Boarding School Culture: A Holistic Approach at Syaikh Zainuddin NW Anjani Islamic Boarding School - Arifin, Bustanul; Habsyi, Irsan; Faizun, Adi; Kholidi, Ahmad Khaerul; irwan, irwan (JUPE : Jurnal Pendidikan Mandala, 2025)
This research is motivated by the problem of low good character among students, which has an impact on immoral actions. The purpose of this investigation is to identify the leadership style of tuan guru in shaping the character of students and to analyze the methods and approaches used by tuan guru in the character formation process. Research is important to provide new insights and solutions related to the character of students, cultural leadership, and a holistic approach. Several previous studies such as: Building Creative, Tolerant, and Responsible Student Characters. Independent Character Development Strategy for Students. The Role of Modern Islamic Boarding Schools in the Formation of Leadership Character. Contribution of Islamic Boarding School Education in Character Formation. Character Education Patterns in Islamic Boarding Schools. Shows that Islamic boarding schools have an important role in shaping the character of students through an integrated approach between academic education and moral values. With the right strategy, students can develop into creative, tolerant, responsible individuals, and have good leadership skills. Research on student character, cultural leadership, and a holistic approach has not specifically explored the integration of character development with cultural leadership and the synergy between local values and character education. This confirms the novelty of this manuscript. The hypothesis proposed in this study is that there is a contribution of cultural leadership and a holistic approach to the character of students. The results of the study indicate that the paternalistic leadership style of Tuan Guru and exemplary behavior in daily behavior have a significant impact on the formation of students' character. In addition, learning methods that integrate local cultural values have proven effective in supporting the characterization process. The conclusion of this study confirms that cultural-based leadership in Islamic boarding schools contributes significantly to building students' character holistically.